PALM KERNEL SHELL AS AN ALTERNATIVE AGGREGATE ON HIGH PERFORMANCE CONCRETE - Purwanti, Heny; Artiningsih, Titik Penta (Journal of Science Innovare, 2018)
Coarse aggregates commonly used in concrete are coarse natural aggregates, which are broken stones or gravel. Continuous rock exploration can cause environmental damage or even more severe ecosystem damage. Therefore it is necessary to substitute an alternative aggregate. Indonesia has the second largest oil palm plantation (Elaeis guineensis Jacq) in the world after Malaysia. Plantations are renewable resources, so palm oil is also potential to be used as an alternative to diesel fuel. Palm kernel shells are palm oil industry wastes which are generally underutilized. Palm kernel shells can be used as an alternative to coarse aggregate, because oil palm shells have the advantage of being hard, tough and good durability due to the high content of lignin and silica dioxide (SiO2), such as hard wood, but low cellulose content so it is not easy rot. The strength of the palm oil shell is quite good. In addition, the aggregate gradation also fulfills the requirements without a breakdown process, which has a thickness of 2-4 mm and a maximum width of 15 mm. The volume of oil palm shells is + 600 kg/m3, so it will produce significant light weight concrete. The concrete studied was concrete with a coarse aggregate of tenera palm kernel shells, with fine aggregates of natural sand, and a Portland Composite Cement (PCC), but the PCC content was reduced and replaced by FA which varied from 0%, 5%, 10 %, 15%, 20 and 25%. Concrete also added superplasticizer (SP). SP is used to reduce water use, because the shell absorbs water. SP levels also vary, namely 0%, 1%, and 1.2%. The weight of the volume of concrete with various levels of fly ash and SP is 1700-1800 kg/m3, so it can be classified as lightweight concrete. Increased FA levels will increase compressive strength, but only up to 10%, after which the strength decreases. Compressive strength of specimens with SP 0% and FA 10% is 17.92 MPa, for SP levels of 1% and FA 10% is 22.15 MPa, while for SP levels of 1.2% and FA 10% is 19.35 MPa . So that it can be concluded that the palm shell as bio-material (renewable resources) can be used as a substitute for natural coarse aggregates. The optimum fly ash level is 10%, and to reduce water use SP 1%. The use of oil palm shells as a substitute for gravel means reducing the waste of the palm oil industry, while reducing rock exposures. In addition, in Indonesia there are many areas where there are no rock sources while oil palm plantations are quite extensive.